Are you experienced? Survival and recovery of trade relations after banking crises - Cosimo Beverelli; Madina Kukenova; Nadia Rocha (World Trade Organization (WTO), 2011)
Using highly disaggregated US import data from 157 countries between 1996 and 2009, we first provide evidence that banking crises negatively affect the survival of trade relations. On average, the occurrence of a banking crisis decreases the rate of survival of trade relations by 13 percent. Moreover, we find that both the size of exports and exporting experience matter for recovery of trade relations after banking crises. Sectoral financial dependence has an experience-specific effect. Relations with more experience recover faster in financially dependent sectors. There is instead no clear evidence indicating effects of size heterogeneity, neither in financially dependent sectors nor in non-financially dependent ones. The results are robust and consistent across alternative econometric models.
Keywords: G01; C41; F14; 330; banking crises; financial dependence; export experience; duration models